Teachers Perceptions of Lesson Study Implementation at Bua Secondary School - Paldy; Dwi Indah, Opik; M, Juwita Crestiani; Hermini; Tangkelangi, Nuur Insan; Sudirman, Andi Mangnguntungi (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This research is descriptive research with a qualitative approach. It aims to find out how the teachers’ perception regarding the implementation of lesson study. There were 4 teachers of Bua Secondary School who were involved as model teachers in LS activities as respondents in this study. The instruments used questionnaire to gain data of the students’ perception and observation sheet for lesson study activities to support the data. The result of this research shows that through lesson study their students be more active, they become innovative and creative to design and implement differentiation learning, and lots of input or suggestion from observers can improve quality of learning, Moreover, they state that by lesson study they got benefit such as: they can design fun and innovative learning, provide fun learning to students, elaboration occurs in the learning strategy, and through lesson study activities can improve the quality of learning so that it is more meaningful and pro-students. Based on the result, it can be concluded that all the respondents have good perception towards the implementation of lesson study at Bua Secondary School.